Nomenclatural notes on Piper pseudonigrum Velayd. and Amalraj (Piperaceae) (Bangladesh Journal of Plant Taxonomy, 2017)
Not available.Keywords: Piper pseudonigrum; Nomenclatural note.Bangladesh J. Plant Taxon. 24(1): 117118, 2017 (June)